2018
DOI: 10.1074/mcp.ra117.000261
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Quantification of Over 2000 O-linked Glycopeptides in Activated Human T Cells with Isotope-Targeted Glycoproteomics (Isotag)

Abstract: Post-translational modifications (PTMs) on proteins often function to regulate signaling cascades, with the activation of T cells during an adaptive immune response being a classic example. Mounting evidence indicates that the modification of proteins by O-linked Nacetylglucosamine (O-GlcNAc), the only mammalian glycan found on nuclear and cytoplasmic proteins, helps regulate T cell activation. Yet, a mechanistic understanding of how O-GlcNAc functions in T cell activation remains elusive, partly because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
181
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(190 citation statements)
references
References 59 publications
(61 reference statements)
8
181
1
Order By: Relevance
“…A degree of internal tag fragmentation was observed with ETD, although this was not seen with all precursor ions. 45 A maximum of 0.1 min chromatographic retention time shift between differentially deuterated isotopes was observed by nanoflow liquid chromatography. This was negligible for isotopic pattern matching due to implementation of spectral bundling (Figure S4).…”
Section: Resultsmentioning
confidence: 96%
“…A degree of internal tag fragmentation was observed with ETD, although this was not seen with all precursor ions. 45 A maximum of 0.1 min chromatographic retention time shift between differentially deuterated isotopes was observed by nanoflow liquid chromatography. This was negligible for isotopic pattern matching due to implementation of spectral bundling (Figure S4).…”
Section: Resultsmentioning
confidence: 96%
“…Together, these studies have identified transcription factors both upstream and downstream of IL-2 that require O-GlcNAc modification for proper function. Interestingly, glycoproteomics approaches used to identify O-GlcNAc modified proteins in activated T cells have uncovered an enrichment for transcription factors [41,42] and RNA metabolism in general [41]. Furthermore, cMyc, which acts downstream of IL-2 and is required for glucose and glutamine intake, requires O-GlcNAc modification for expression [34].…”
Section: O-glcnac In T Cell Activationmentioning
confidence: 99%
“…We next evaluated the proximity-directing ability of nGFP (13) in HEK293T cells co-expressing with GFP-Flag-JunB-EPEA, a transcription factor carrying multiple O-GlcNAc sites (15), as the target protein. Immunoprecipitation of GFP-Flag-JunB-EPEA and probing for O-GlcNAc revealed an increase in O-GlcNAc levels on the target protein that was dependent on the co-transfected nGFP(13) ( Figure 2C).…”
Section: Design and Expression Of Proximity-directed Nanobody-ogt(13)mentioning
confidence: 99%
“…In contrast to most PTMs, O-GlcNAc is installed and removed by only two enzymes: O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA), which modify over 3,000 protein substrates ( Figure 1) (11)(12)(13)(14)(15). O-GlcNAc is critical to cellular function as deletion of OGT in mice is embryonic lethal (16), deletion of OGA leads to perinatal death (17), and the conditional deletion of OGT in numerous cell types leads to senescence and apoptosis (18).…”
Section: Introductionmentioning
confidence: 99%